الحوار القرآني لترسيخ عقيدة الإيمان باليوم الآخر - حجرى، سليمان محمد حمود الحجري (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2015)
The main objective of this thesis is to provide a theoretical study on the dialogue techniques used in the holy Qur'an to strengthen one's belief in the Hereafter. The thesis discusses in detail the concept of dialogue, its limits and ethics. The study is carried out within the framework of the educational methods of reinforcing people's belief in the Hereafter, taking into consideration the ideological, moral and psychological factors influencing the addressees. The study adopts the historical and the discourse analysis methods to address the problem at hand . The findings are used to set forth the best dialogic methods for the strengthening of the Islamic creed and the inculcation of high morals. The thesis is divided into two parts. Part I comprises three chapters. The first chapter is an introductory chapter which defines the concept of dialogue and a number of related terminologies. The second chapter discusses some practical examples of the use of the dialogue technique in the field of Aqeedah. The third chapter identifies some of the methods employed in the holy Qur'an to strengthen one's belief in the Hereafter. It also discusses the educational methods used and the obstacles that may exist. The first chapter in Part II discusses the intellectual dimension of dialogue and illustrates the rational evidences of Allah's ability to resurrect mankind after death. The second chapter in Part II, focuses on the moral dimension of dialogue. It discusses the role of morality in dialogue and the negative effects of bad morals on dialogue. The study has reached several conclusions, the most important of which is the fact that the Qur'an has a unique and comprehensive method of strengthening one's belief in the Hereafter. The study concluded that dialogue is an ideal technique to reinforce one's belief. Move over the study concluded that it is an ideal solution for addressing interpersonal disputes and for closing the gaps that exist in society. Nevertheless, the success of dialogue technique depends on a strict adherence to the moral standards prescribed in Islam